2020
DOI: 10.1016/j.bse.2020.104043
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolates in Reseda lutea L.: Distribution in plant tissues during flowering time

Abstract: Reseda lutea L. belongs to the Resedaceae family included in the order of Brassicales. R. lutea is a plant worthy of investigation on an ecological level for its ability to adapt to extreme environmental conditions and for its capacity to attract honeybees and wild pollinators. In the ancient pharmacotherapy it was also known for its healing properties. R. lutea glucosinolates (GSLs) were investigated by HPLC-UV considering their accumulation pattern and their quality profiles during flowering time. 3-hydroxyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…Fragments from the elimination of anhydrorhamnose, anhydroglucose, and thioglucose (fragment h ) were observed, with the characteristic fragment m / z 334 resulting from the loss of glucose ( m / z 180). Glucolepigramin ( 22 ) was identified only in the flower (8.66 µmol g − 1 DW) using desulfoglucolepigramin as a standard isolated from Lepidium graminifolium [ 38 ], corroborating a recent discovery [ 29 ].…”
Section: Resultssupporting
confidence: 62%
“…Fragments from the elimination of anhydrorhamnose, anhydroglucose, and thioglucose (fragment h ) were observed, with the characteristic fragment m / z 334 resulting from the loss of glucose ( m / z 180). Glucolepigramin ( 22 ) was identified only in the flower (8.66 µmol g − 1 DW) using desulfoglucolepigramin as a standard isolated from Lepidium graminifolium [ 38 ], corroborating a recent discovery [ 29 ].…”
Section: Resultssupporting
confidence: 62%
“…Resedaceae family, Reseda lutea L. -the fresh stems, roots and leaves have a pleasant mustard scent and are used as a spice and flavoring agent. The roots, leaves, stems and fruits contain mustard essential oil; the seeds contain fatty oil, which includes tocopherol; the leaves contain a flavone derivative, the pigment luteolin (Pagnotta et al 2020). R. lutea -contains the flavone luteolin.…”
Section: Fabаceae Familymentioning
confidence: 99%
“…Many studies demonstrated the existence of flavonoids, anthocyanins, and α-glycosides in the aerial parts of R. lutea [ 18 20 ]. R. lutea was included in lists of interesting species at the ethnopharmacological level because of its healing properties, antitumor, anti-HIV, cytotoxic, antibacterial, antiinflammatory, and antioxidant effects [ 7 , 16 , 21 – 23 ]. Kaempferol isolated from R. lutea is a flavonoid antioxidant found in fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%